Optical Soliton Solutions of Fokas-Lenells Equation via (m + 1/G’)- Expansion Method - Bulut, Hasan; Khalid, Ban Jamal (Journal of Advances in Applied & Computational Mathematics, 2020)
In this research paper, we investigate some novel soliton solutions to the perturbed Fokas-Lenells equation by using the (m + 1/G’) expansion method. Some new solutions are obtained and they are plotted in two and three dimensions. This technique appears as a suitable, applicable, and efficient method to search for the exact solutions of nonlinear partial differential equations in a wide range. All gained optical soliton solutions are substituted into the FokasLenells equation and they verify it. The constraint conditions are also given.